Radio frequency shielding of thin aluminized plastic filters investigated for the ATHENA X-IFU detector - Lo Cicero, Ugo; Lo Cicero, Giuseppe; Puccio, Elena; Montinaro, Nicola; Gulli, Daniele; Todaro, Michela; Calandra, Enrico; Törmä, Pekka; Cuttaia, Francesco; Villa, Fabrizio; Ferruggia Bonura, Salvatore; Lullo, Giuseppe; et al. (SPIE, 2018)
The X-ray Integral Field Unit (X-IFU) is one of the two detectors of the ATHENA astrophysics space mission approved by ESA in the Cosmic Vision 2015-2025 Science Programme. The X-IFU consists of a large array of transition edge sensors (TES) micro-calorimeters covering a field of view of ~5’ diameter, sensitive in the energy range 0.2-12 keV, and providing a spectral resolution of 2.5 eV at 7 keV. Both the TES and superconducting quantum interference devices (SQUID) based read-out electronics are very sensitive to electromagnetic interferences (EMI), and a proper shielding of the focal plane assembly (FPA) is required to prevent a deterioration of the energy resolution. A set of thin filters, highly transparent to X-rays, will be mounted on the FPA and on the cryostat thermal shields in order to attenuate the infrared radiative load, and to protect the detector from contamination. Some of these filters are also aimed at providing proper radio frequency (RF) shielding in the frequency range of the satellite telemetry downlink antenna. In addition, filters should also be effective in shielding any RF interference generated by other on-board electronics. In this paper, we present results from RF measurements performed on thin plastic foils coated with an aluminum layer, with and without metal meshes, and identify the filter characteristics matching the RF shielding requirements.